Gentrification and touristification trends in the historic center of Madrid. The case of Lavapiés - Mazorra Rodríguez, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article studies how the processes of gentrification and touristification associated with the globalization of the economy, in the case of Madrid (Spain), has increased social inequality. It uses a mixed methodology, based on the analysis of data, the development of in-depth interviews, and historiographicalrevision. The research centers its attention on the transformation of Lavapiés, a central neighborhood of the city of Madrid. It focuses, on the one hand, on identifying and describing whathave been the fundamental effects of these trends on the social and urban structure of the city of Madrid, and on the other hand, on exposing and analyzing what have been the mainexperiences and discourses created by the actors linked to the neighborhood, with respect to its transformation. Thesedynamics have consolidated the advance towards a model of a dual city, characterized by the polarization of its social and urban structure, formed by a wealthy north-east and a poor and vulnerable south-east.